The Art of the Storyteller Hakob Mndzuri - Avagyan, Artsrun (Bulletin of Yerevan University B: Philology, 2024)
The article presents the manifestations of the literary talent of Hakob Mndzuri, one of the greatest Armenian writers, highlighting the content and pictorial features of his stories. At one time, Mndzuri lost his native land and all members of his family and was forced to live his entire life in Constantinople. Memories of his birthplace Armtan and its inhabitants were part of his life. He has left a valuable literary legacy about his native land and his loved ones. The forms of narration with which the writer wrote his works are distinguished by brevity, emphasizing the details of “small events” that occurred in life, an abundance of new methods of narration, depth of subtext, originality of the created characters and great love shown to his native nature. Everything that Mndzuri wrote is a reflection of his thoughts and feelings, as a result of which in his stories there is more Mndzuri the man than the writer-author. One of the features of Mndzuri’s stories is the transformation of the reader into a participant in the narrated events, the “illogicality” of interruptions and deviations in the development of the plot, the lyricism of descriptions, clarity of speech, an abundance of colorful images, personification of inanimate objects and the animal world, thanks to which the writer introduces us to the region of Western Armenia, Armtan and its environs, saying that this is the motherland of his and our people, which should never be forgotten.